Enchanted: Aino Kallas’s Legatonland Memoirs of London between the Wars - Pilvi Rajamäe (Interlitteraria, 2020)
The Finnish-Estonian writer Aino Kallas lived in London between 1922 and 1934, being the wife of the first Estonian ambassador to the Court of St James’s. In 2011 her memoirs of these years were published in Estonian translation under the title Londoni võlus (Enchanted by London). Being a romantic and a modernist, Kallas in her memoirs combines a heightened sensitivity with the rigours of the modernist style in order to convey in striking images what she recalls about persons and events in London between the wars. The article below will look at some of these characteristic images that convey her vision of London that is full of enchantment.